Adaptive architecture as mediator between humans and earth - Marie Ulber; Mona Mahall (Agathón)
This paper describes the potential of adaptive architecture to mediate not only technically but also socially and aesthetically between humans and the environment. Compensating global change through architecture does not change human behaviour; the challenge is to involve and activate each inhabitant. By implementing the principle of adaptation in all dimensions, a step towards a healthy and resilient relationship between humans and earth can be taken. In this holistic approach, historical and contemporary projects in Architecture and Art are discussed and systemic, explorative, social and aesthetic perspectives are taken. As a mediator adaptive architecture makes a global system experienceable in the local, supports its inhabitants to improve their relationship to the Earth and adapt.